The evolution of genome-scale models of cancer metabolism - Lewis, Nathan E.; Abdel-Haleem, Alyaa M. (Frontiers in Physiology, 2013)
The importance of metabolism in cancer is becoming increasingly apparent with the identification of metabolic enzyme mutations and the growing awareness of the influence of metabolism on signaling, epigenetic markers, and transcription. However, the complexity of these processes has challenged our ability to make sense of the metabolic changes in cancer. Fortunately, constraint-based modeling, a systems biology approach, now enables one to study the entirety of cancer metabolism and simulate basic phenotypes. With the newness of this field, there has been a rapid evolution of both the scope of these models and their applications. Here we review both the various constraint-based models built for cancer metabolism and how their predictions are shedding new light on basic cancer phenotypes, pathway differences between tumors, and putative anti-cancer targets. As the field continues to evolve, the scope of these genome-scale cancer models must expand beyond central metabolism to address questions related to the many other processes contributing to tumor development and metastasis.